PENEGAKAN HUKUM TERHADAP PELANGGARAN MUATAN BARANG DI WILAYAH HUKUM KEPOLISIAN RESOR DAIRI - Febrianda Raja; Davit Rahmadan; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The development of transportation which is relatively very rapid is carried out through transportation technology which is characterized by its main characteristics namely increasing vehicle speed and enlargement of transport capacity. So that all community activities are based on applicable laws, as well as on traffic rules. Traffic is a vital means, because it is directly related to transportation.This thesis, namely; First law enforcement for violations of cargo in the Dairi Resort Police jurisdiction. Secondly, there are obstacles to law enforcement against violations of cargo in the Dairi Resort Police jurisdiction. Third, efforts to overcome obstacles to the cargo cargo in the Dairi Resort Police jurisdiction.This research is classified in the type of sociological research, which examines certain legal phenomena by analyzing them, then seeking a solution to the problems that arise in the phenomena concerned. This research was conducted at the Dairi Resort Police, namely the Dairi Resort Police Traffic Unit and the Dairi District Transportation Agency. Meanwhile, the population and sample are all parties related to the problem examined in this study. Data sources used are primary data, secondary data and tertiary data, as well as data collection techniques in this study by observation, interview, submitting a list of questions and document studies.From the results of the study it can be concluded that the Lawsuits Against Offloading of Goods Overloaded in the Dairi Resort Police jurisdiction is still not going well because the legal process does not match the legal process in force by the Dairi Resort Police apparatus. Inhibiting factors occur criminal acts of violation of the cargo of goods, namely internal and external factors that are interrelated in supporting the occurrence of criminal acts of violation of the cargo of goods.Keywords : Law Enforcement – Violations - Cargo